Gold nanomaterials for optical biosensing and bioimaging. Issue 10 (14th April 2021) - Si, Peng; Razmi, Nasrin; Nur, Omer; Solanki, Shipra; Pandey, Chandra Mouli; Gupta, Rajinder K.; Malhotra, Bansi D.; Willander, Magnus; de la Zerda, Adam
Abstract : In this minireview, we discuss the emerging optical biosensing and bioimaging techniques that leverage the unique optical properties of gold nanoparticles. Abstract : Gold nanoparticles (AuNPs) are highly compelling nanomaterials for biomedical studies due to their unique optical properties. By leveraging the versatile optical properties of different gold nanostructures, the performance of biosensing and biomedical imaging can be dramatically improved in terms of their sensitivity, specificity, speed, contrast, resolution and penetration depth. Here we review recent advances of optical biosensing and bioimaging techniques based on three major optical properties of AuNPs: surface plasmon resonance, surface enhanced Raman scattering and luminescence. We summarize the fabrication methods and optical properties of different types of AuNPs, highlight the emerging applications of these AuNPs for novel optical biosensors and biomedical imaging innovations, and discuss the future trends of AuNP-based optical biosensors and bioimaging as well as the challenges of implementing these techniques in preclinical and clinical investigations.